Human rights of refugee-survivors of sexual and gender-based violence with communication disability. (2nd January 2018) - Marshall, Julie; Barrett, Helen
Abstract: Article 19 of the Universal Declaration of Human Rights (United Nations, 1948 ) states that all people have the right to seek, receive and impart information using any means. Ensuring that people with communication disability achieve this right is inherently challenging. For people with communication disability, who are refugee-survivors of sexual and gender-based violence (SGBV), additional human rights are challenged, including the right to education, protection from discrimination, a safe place to live, security of person and legal protection. Their experiences and needs, however, are poorly understood. This paper reports on a literature review of the intersectionality between SGBV, being a refugee and having a communication disability, and a preliminary investigation of the situation of refugee-survivors of SGBV with communication disability, in Rwanda. The project involved 54 participants, including 50 humanitarian and partner organisation staff and four carers of refugees with communication disabilities, from two locations (camp-based and urban refugees). Findings from both revealed that, for people with communication disability, barriers are likely to occur at each step of preventing and responding to SGBV. Moreover, stigmatisation of people with communication disability challenges SGBV prevention/support and people with communication disability may be targeted by SGBV perpetrators. SGBV service providers acknowledge their lack of knowledge and skills about communication disability, but wish to learn. Findings highlight the need for increased knowledge and skill development, in order to improve the situation for refugee-survivors of SGBV with communication disability.